2013
DOI: 10.1021/am4033857
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of Gold Nanorods in Breast Cancer Cells: Uptake, Lysosome Maturation, and Elimination

Abstract: Gold nanorods (AuNRs) have been largely investigated driven by their promising potentials in drug delivery, imaging, and photodynamic therapy because of their distinctive physicochemical properties. It is widely known that AuNRs can be taken up by different cells, however, the trafficking of the nanorods in cells are less known. In this work, the behaviors and fate of AuNRs in the human breast cancer cell line MDA-MB-231 were intensively probed by transmission electron microscopy (TEM) with detailed time resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 41 publications
4
46
1
Order By: Relevance
“…Although there are limitations to analysis of uptake via TEM (slice-by-slice imaging), these qualitative observations have been observed before and quantified in other cases by more sophisticated analyses (36). Occasional lysosomal escape has been reported with positively and negatively charged gold nanorods before, and it was found that PEGylated gold nanospheres escaped into the cytoplasm of macrophages and lung cells (PEG NPs escaped more than citrate NPs in the case of the lung cell study) (36)(37)(38).…”
Section: Discussionmentioning
confidence: 97%
“…Although there are limitations to analysis of uptake via TEM (slice-by-slice imaging), these qualitative observations have been observed before and quantified in other cases by more sophisticated analyses (36). Occasional lysosomal escape has been reported with positively and negatively charged gold nanorods before, and it was found that PEGylated gold nanospheres escaped into the cytoplasm of macrophages and lung cells (PEG NPs escaped more than citrate NPs in the case of the lung cell study) (36)(37)(38).…”
Section: Discussionmentioning
confidence: 97%
“…In another study employing sequential transmission electron microscopy (TEM) of MDA-MB-231 cells, AuNRs were taken up by receptor-mediated endocytosis and formed endocytotic vesicles that evolved into lysosomes and autophagosomes. Reuptake of the eliminated particles was observed after exocytosis [22]. …”
Section: Characteristics Of Gold Nanoparticlesmentioning
confidence: 99%
“…In line with these findings, clusters of nanorods in the perinuclear region were also found to be localized in lysosomes in human mammary carcinoma cell lines. 36 Finally, the quantification of gold nanoparticles that are taken up specifically by tumor cells or tumor cell clusters is important to estimate the amount of nanoparticles that is necessary to improve noninvasive in vivo imaging of tumors in mice and humans. In our setup, we could detect aggregates in perinuclear areas of around 1-2 µm in diameter.…”
mentioning
confidence: 99%